An erythrocyte vesicle protein exported by the malaria parasite promotes tubovesicular lipid import from the host cell surface. - Pamela A Tamez; Souvik Bhattacharjee; Christiaan van Ooij; N Luisa Hiller; Manuel Llinás; Bharath Balu; John H Adams; Kasturi Haldar (PLoS Pathogens)
Plasmodium falciparum is the protozoan parasite that causes the most virulent of human malarias. The blood stage parasites export several hundred proteins into their host erythrocyte that underlie modifications linked to major pathologies of the disease and parasite survival in the blood. Unfortunately, most are 'hypothetical' proteins of unknown function, and those that are essential for parasitization of the erythrocyte cannot be 'knocked out'. Here, we combined bioinformatics and genome-wide expression analyses with a new series of transgenic and cellular assays to show for the first time in malaria parasites that microarray read out from a chemical perturbation can have predictive value. We thereby identified and characterized an exported P. falciparum protein resident in a new vesicular compartment induced by the parasite in the erythrocyte. This protein, named Erythrocyte Vesicle Protein 1 (EVP1), shows novel dynamics of distribution in the parasite and intraerythrocytic membranes. Evidence is presented that its expression results in a change in TVN-mediated lipid import at the host membrane and that it is required for intracellular parasite growth, but not invasion. This exported protein appears to be needed for the maintenance of an essential tubovesicular nutrient import pathway induced by the pathogen in the host cell. Our approach may be generalized to the analysis of hundreds of 'hypothetical' P. falciparum proteins to understand their role in parasite entry and/or growth in erythrocytes as well as phenotypic contributions to either antigen export or tubovesicular import. By functionally validating these unknowns, one may identify new targets in host-microbial interactions for prophylaxis against this major human pathogen.